Therapeutic efcacy of preparations in the form of a solution for external use based on imidacloprid, pyriproxyfen and moxidectin at nematodosis of dogs and cats - O. N. Tochieva; M. V. Arisov (Российский паразитологический журнал, 2022)
The purpose of the research is to study the therapeutic efcacy of drugs in the form of a solution for external use based on imidacloprid, pyriproxyfen and moxidectin against gastrointestinal nematodes and Diroflaria spp. microflaria in dogs and cats.Materials and methods. . The studies were carried out on the basis of VNIIP (fl. Federal State Budgetary Scientifc Institution FNTs VIEV RAS) on dogs and cats of diﬀerent sex and age, body weight spontaneously infected with parasites. The diagnosis, as well as the eﬀectiveness of the drugs, was confrmed in a complex manner based on the anamnestic and epizootological data, the clinical picture and laboratory research methods (detection of helminth eggs in the animal's feces using the Fülleborn method with subsequent diﬀerentiation, microscopy of animal blood smears to detect microflariae). To rule out infection of animals (dogs) with babesia, blood samples were taken and a laboratory analysis was performed to detect parasites (Babesia canis).Results and discussion. 100% eﬀectiveness of Insacar Total C (for dogs) and Insacar Total K (for cats) has been established for nematodes of the gastrointestinal tract (toxocarosis, toxascariosis, uncinariosis, hookworm, trichuriosis) and diroflariosis (the initial stage of the disease). Side eﬀects and complications after treatment of animals with drugs were not revealed